Formação humana em espaço não escolar: a perspectiva da escola bíblica dominical da Igreja Assembleia de Deus, em Salvaterra/PA - FROTA, José Fabiano de Sousa (2024)
Human formation is a continuous, complex, and multifaceted process that involves the development of skills, knowledge, and values that shape the individual in his personal, social, and all his dimensions. It can occur in different contexts and spaces such as family, school, community, church, and/or work. In this context, this study aims to analyze the perspective of human formation developed by the Sunday School (SS) of the Assembly of God Church (IAD), in Salvaterra/PA. The investigation was guided by a qualitative approach, operationalized through a field research of the descriptive type, in which a questionnaire with open-ended questions was used for 9 participants who attend SS in different congregations of the study locus. The study was anchored in the conceptions of education and pedagogy of Saviani (2005), Gohn (2006), Severo (2018), Padilha (2007), Libâneo (2010), Ri and of Sunday School by Andrade (2000) and Silva (2014), among others. From the data analysis, it was possible to attest that the SS of the IAD of Salvaterra/PA is guided by a conception of Christian, humanizing, dialogical, inclusive, and multigenerational formation and pedagogy. Its formative action is intentional, systematic, and obeys its own methodological and organizational principles and procedures. It has the Bible as its basic document from which the programmatic contents to be taught originate. The reflections of the formative process have affected aspects of personal human life (spirituality, ethical and moral behavior, relationships, self-knowledge) and social life (citizenship, social participation), highlighting the importance of education, whether it be in formal or informal spaces, as a key to individual development, as well as the potential of SS as a relevant formative space/time within the actions of the Evangelical Assembly of God Church in Salvaterra-PA.